Guidelines for Health System Management for Cambodia, Laos, Myanmar, and Vietnam (CLMV) Medical Tourists in the Regional Provinces of Thailand - Srirak, Chainarong; Sukjai, Patthaphon (Ikatan Dokter Indonesia Wilayah Jawa Timur, 2023)
Introduction: Medical tourism refers to any person who travels cross-border to a foreign country to receive medical services. The Thai government has set a strategy to make Thailand a medical hub to drive economic growth in the future. The purpose of this research was to conduct an analysis of health system management for Cambodia, Laos, Myanmar, and Vietnam (CLMV) medical tourists in regional provinces of Thailand. Methods: This research was qualitative research. The in-depth interview was conducted with 25 cases, and the focus group was conducted with 30 representatives of government agencies and private entrepreneurs involved in policies, together with document analysis. The content analysis was applied for data analysis. Results: It was found that the guidelines for health system management for CLMV medical tourists in regional provinces, namely adjusting the medical payment system, tightening screening of treatment eligibility, cooperating internationally in the management of the International Health Insurance Fund, establishing a medical fund for those who do not have Thai citizenship; establish foreign patients department in government hospitals; and control appropriate and fair service rates. Conclusion: Practical short-term factors include promoting targeted niche markets, establishing marketing partnerships with other businesses, supporting medical tourism, making a database of expertise of hospitals in Thailand and training doctors with specialized expertise, especially international programs, promoting research, development and production of medical equipment and medical supplies, and encourage private hospitals in Thailand to be certified important in increasing Cambodia, Laos, Myanmar and Vietnam (CLMV) Medical Tourists in the Regional Provinces of Thailand.